2019
DOI: 10.1136/bmjopen-2018-026602
|View full text |Cite
|
Sign up to set email alerts
|

Molidustat for the treatment of renal anaemia in patients with dialysis-dependent chronic kidney disease: design and rationale of three phase III studies

Abstract: IntroductionNew medications for anaemia associated with chronic kidney disease (CKD) are desirable, owing to the limitations of erythropoiesis-stimulating agents (ESAs), the current standard of care. Molidustat is a novel hypoxia-inducible factor prolyl-hydroxylase inhibitor that stimulates erythropoietin production, predominately in the kidney. We report methodological details of three phase III trials, named MolIdustat once dailY improves renal Anaemia By Inducing erythropoietin (MIYABI), designed primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…Although PK and PD (effect on EPO) parameters of molidustat in healthy volunteers were affected by oral administration of iron(II) sulphate or iron(II) glycine sulphate immediately before molidustat, these effects were reduced by temporal separation of drug intake. This is currently being investigated in ongoing phase 3 clinical trials [8,9]. Calcium supplement (investigated as calcium acetate) co-administration had no relevant effect on the pharmacokinetics or pharmacodynamics of molidustat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PK and PD (effect on EPO) parameters of molidustat in healthy volunteers were affected by oral administration of iron(II) sulphate or iron(II) glycine sulphate immediately before molidustat, these effects were reduced by temporal separation of drug intake. This is currently being investigated in ongoing phase 3 clinical trials [8,9]. Calcium supplement (investigated as calcium acetate) co-administration had no relevant effect on the pharmacokinetics or pharmacodynamics of molidustat.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of HIF-PH results in stabilization of HIF, which leads to endogenous production of EPO and, ultimately, stimulation of erythropoiesis [7]. Molidustat is an orally bioavailable HIF-PH inhibitor being investigated in phase 3 clinical trials in patients with renal anaemia, including patients receiving dialysis treatment [8,9]. The phase 2 DIALOGUE (DaIly orAL treatment increasing endOGenoUs Erythropoietin) programme, which included three studies with a 16week treatment duration and two extension studies, assessed the safety and efficacy of molidustat in different populations of patients with renal anaemia [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, molidustat restored renal EPO production with minor stimulation of hepatic EPO [121,123]. Moreover, it heightened plasma EPO and EPO mRNA in the kidney prevented the reduction in hematocrit and corrected Hb level [121].…”
Section: New Strategies Of Anemia Treatmentmentioning
confidence: 96%
“…PHD2 knockdown did not affect the formation of MBL oligomers further supporting that prolyl hydroxylation of collagen-like domain of MBL as well as oligomerization of MBL is CP4H dependent and PHD independent. Finally, we used several PHD inhibitors which are currently undergoing phase III clinical trials 21,34 (roxadustat, vadadustat and molidustat) at concentrations which stabilize HIF1α in a robust manner. Crystallography studies by Yeh et al 35 showed that the mechanism of action for these drugs was via chelation to the active site iron.…”
Section: Discussionmentioning
confidence: 99%